Isolation of Coxiella burnetii from an acromioclavicular infection with low serological titres. (August 2018) - Melenotte, Cléa; Bart, Géraldine; Kraeber-Bodere, Francoise; Cammilleri, Serge; Le Goff, Benoit; Raoult, Didier
Highlights: Coxiella burnetii was isolated from an acromioclavicular synovial biopsy. C. burnetii acromioclavicular infection is a new clinical entity. Evidence of persistent C. burnetii infectious foci with low serological titres was found. This report highlights the crucial role of PET imaging in identifying the deep infectious focus. Abstract: Coxiella burnetii acromioclavicular infection is a new infectious focus, evidenced here for the first time using the gold standard, culture. Positron emission tomography had a crucial role in identifying the deep infectious focus, even when C. burnetii serological titres were low.